Role of cyclooxygenase-2 in Trypanosoma cruzi survival in the early stages of parasite host-cell interaction - Moraes, Karen C. M. [UNESP]; Diniz, Livia F.; Bahia, Maria Terezinha (Fundaco Oswaldo Cruz, 2015)
Chagas disease, caused by the intracellular protozoan Trypanosoma cruzi, is a serious health problem in Latin America. During this parasitic infection, the heart is one of the major organs affected. The pathogenesis of tissue remodelling, particularly regarding cardiomyocyte behaviour after parasite infection and the molecular mechanisms that occur immediately following parasite entry into host cells are not yet completely understood. When cells are infected with T. cruzi, they develop an inflammatory response, in which cyclooxygenase-2 (COX-2) catalyses rate-limiting steps in the arachidonic acid pathway. However, how the parasite interaction modulates COX-2 activity is poorly understood. In this study, the H9c2 cell line was used as our model and we investigated cellular and biochemical aspects during the initial 48 h of parasitic infection. Oscillatory activity of COX-2 was observed, which correlated with the control of the pro-inflammatory environment in infected cells. Interestingly, subcellular trafficking was also verified, correlated with the control of Cox-2 mRNA or the activated COX-2 protein in cells, which is directly connected with the assemble of stress granules structures. Our collective findings suggest that in the very early stage of the T. cruzi-host cell interaction, the parasite is able to modulate the cellular metabolism in order to survives.
Keywords: Cardiac cells; Chagas disease; Enzyme activity; Fluorescence microscopy; Pro-inflammatory process; Subcellular trafficking